Blend-in fairness and equal split - Dinko Dimitrov; Ching-jen Sun (International Journal of Game Theory, 2025)
Blending in with others is a possible self-serving motivation when people participate in cooperative situations. We use this motivation to formulate a corresponding fairness principle, combine it with rather weak standard axioms from cooperative game theory, and show that it leads to equal split of coalitional gains. The same normative principles characterize this solution when only cohesive games (where it is optimal for the coalition of all players to form) are considered.
Keywords: A13; C71; D63; D91; 330; Blend-in fairness; Cohesive games; Cooperative games; Equal division solution